ICHSF2014 - Huh, H.; Tekkaya, A. E. (Technische Universität Dortmund, 2014)
Since the first ICHSF, which was held in 2004 at the Technische Universität Dortmund, Germany, this biannual conference has grown into one of the major events for high speed forming technologies and its applications. This meeting series is now being organized with the support of the International Impulse Forming Group (I2FG) that was formed in October 2008 through the vision of Professor Erman Tekkaya. His goal was to model this in many ways after the International Cold Forging Research Group which has been instrumental in applying cold forging to wide manufacturing practice. The public face of this site can be found at http://www.i2fg.org with useful information as well as the proceedings of all the ICHSF meetings. This 6th conference is organized as a joint event of the Department of Mechanical Engineering of KAIST (Korea Advanced Institute of Science and Technology) and the Institute of Forming Technology and Lightweight Construction of Technische Universität Dortmund.
6th International Conference on High Speed Forming
High Speed Forming 2014
Keywords: High Speed Forming; Electromagnetic forming; 620; 670